Intellectual Education in the Pedagogical System of Andrii Sheptytskyi (1914–1939) - Anatoliy Vykhrushch (Pedagogical Discourse, 2020)
The article describes the features of the pedagogical system, in particular the most important aspects of intellectual education of a personality, based on the creative heritage of Andrii Sheptytskyi. The theoretical foundations of the development of intellect are considered from the point of view of systematic approach. The attention is focused on the issues of mutual spiritual books reading both in churches and families, as well as on the need for adult education, features of lecturing skills, psychological aspects of the author’s arguments, the importance of scientific schools, the dynamics of the main values in the process of society’s development, the ratio of knowledge, education and wisdom, creativity. The innovative character of the school of prayer is highlighted. Each word of prayer is considered at such a high level, which is an example for modern researchers. An important conclusion about the teaching of philosophy should be taken into account, in the context of the problem under study, for the pedagogy of higher education.